Lettuce Growth Response Against Hydroponic Nutrient Film Technique System Type of Nutrition - Handika, Caca; Budi, Setia; ., Nurjani (Fakultas Pertanian Universitas Tanjungpura, 2020)
This Research aims find out at the differences of various types of nutrition given to lettuce plants and find out the best types of nutrients uses in responding and yielding Lettuce hydroponic plants NFT system. The study was conducted at the Greenhouse Kampong Hidropon Sungai Raya Dalam KM 4 Pontianak City. The research began on September 24, 2018 until November 5, 2018. The design used in this study consisted of 5 levels of treatment without repetition, each treatment contained 20 plant samples so that there were a total of 100 plants. The treatments in the study were A = Goodplant Nutrient, B = Best Harvest, C = Hydroponic Cheers, D = West Borneo MIX, E = Hydroponic Kampong. The observed variables were number of leaves (strands), plant height (cm), total fresh weight (g), crown fresh weight (g), root volume cm ³), and plant dry weight (g). The results of this study showed that various types of nutrition significantly affected all observed variables with NPK ratios of 24.6%, 7.4%, 34.9%, namely the Goodplant nutritional treatment gave the best average treatment for all observed variables. Keywords: Hydroponics, Nutrition Type, Lettuce, NFT